2016
DOI: 10.1002/hed.24613
|View full text |Cite
|
Sign up to set email alerts
|

Differences in patterns of survival in metastatic adenoid cystic carcinoma of the head and neck

Abstract: Metastatic ACC is not always an indolent disease. © 2016 Wiley Periodicals, Inc. Head Neck 39: 456-463, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 33 publications
(103 reference statements)
2
31
0
Order By: Relevance
“…Generally, ACC is being portrayed as an indolent disease; however, it has become clear that this is not always the case . We fully acknowledge that the rarity and the small number of patients represent a significant limitation of our study.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Generally, ACC is being portrayed as an indolent disease; however, it has become clear that this is not always the case . We fully acknowledge that the rarity and the small number of patients represent a significant limitation of our study.…”
Section: Discussionmentioning
confidence: 93%
“…The MYB‐NFIB fusion results in an increased expression of the protein Myb . Myb is important for the growth of multiple solid tumors, and MYB protein overexpression in ACC is associated with a more aggressive clinical course . For example, Mitani et al reported that the level of MYB expression in identical histological subtypes of ACC is associated with a shorter survival time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 However, solid component is associated with adverse outcome. 8 Necrosis and vascular invasion may not be seen commonly. To highlight epithelial component, immunohistochemical (IHC) markers like CK7 and CAM5.2 may be used while myoepithelail component may be highlighted by SMA and S100 IHC markers.…”
Section: Discussionmentioning
confidence: 99%